Celiac Plexus Neurolysis Using Three Different Techniques for Upper Abdominal Metastatic Pain: Comparison the Effectiveness of the Block (Bangladesh Medical Journal, 2014)
33 patients [13 female] with metastatic intractable upper Abdominal Cancer Pain were treated with celiac plexus neurolytic block with 60% alcohol. Aim of study is to observe the effectiveness of three different techniques of celiac plexus block, unilateral paravertibral, bilateral paravertibral and Paravertibral transaortic approach of celiac plexus blocks under C- arm guidance. Satisfactory pain relief occurs in all three techniques but out- come of transaortic approach a little better than other methods. Pain intensity was assessed by VRS and VAS Scale. Celiac plexus blocks are a suitable technique for upper abdominal visceral metastatic pain. Its effects are prolonged and also increase bowel movement, improve appetite and reduced morphine consumption. This is an initial study and numbers of subject are few. So more study required to get conclusive result. Skilled manpower and appropriate case selection is mandatory for successful results. DOI: http://dx.doi.org/10.3329/bmj.v41i2.18800 Bangladesh Medical Journal 2012 Vol. 41 No. 2: 23-26